Understanding Purchase Intention through Customer Relationship Management, Brand Equity, and Perceived Value: A Qualitative Study of Modern Retail Consumers in Sumatra - Lukmanul Hakim; Mon Korcharoen; Tibrani Tibrani (FOUNDAE (Foundation of Advanced Education), 2026)
In the increasingly competitive modern retail context, understanding the formation of purchase intentions has become essential. Accordingly, this study aims to explore how purchase intentions are shaped through customer relationship management (CRM), brand equity, and perceived value, while also considering the roles of perceived product quality and price perception among modern retail consumers in Sumatra. To achieve this objective, an exploratory qualitative approach was employed to capture consumers’ experiences and subjective interpretations in the purchase decision-making process. Data were collected through semi-structured in-depth interviews with regular customers of modern retail outlets in Sumatra and subsequently analyzed using thematic analysis to identify recurring patterns and key themes. The findings indicate that purchase intentions are formed through an integrative evaluative process rather than through isolated assessments of product attributes. In this process, CRM fosters trust and emotional comfort, while brand equity reduces perceived risk by providing a sense of consistency and reliability. Furthermore, perceptions of product quality and price are interpreted contextually, shaping consumers’ judgments of fairness and functional value. These elements ultimately converge in perceived value, which acts as a central mechanism linking consumer experiences to purchase intentions. Overall, this study contributes to the marketing literature by offering a more context-sensitive understanding of purchase intention formation and provides practical insights for retailers in developing relationship-oriented and value-based strategies.